Determinants of business success: an examination of Asian-owned businesses in the United States - Alicia M. Robb; Robert W. Fairlie (Institute for the Study of Labor (IZA), 2007)
Using confidential and restricted-access microdata from the U.S. Census Bureau, we find that Asian-owned businesses are 16.9 percent less likely to close, 20.6 percent more likely to have profits of at least 10,000, and 27.2 percent more likely to hire employees than white-owned businesses in the United States. Asian firms also have mean annual sales that are roughly 60 percent higher than the mean sales of white firms. Using regression estimates and a special non-linear decomposition technique, we explore the role that class resources, such as financial capital and human capital, play in contributing to the relative success of Asian businesses. We find that Asian-owned businesses are more successful than white-owned businesses for two main reasons - Asian owners have high levels of human capital and their businesses have substantial startup capital. Startup capital and education alone explain from 65 percent to the entire gap in business outcomes between Asians and whites. Using the detailed information on both the owner and the firm available in the CBO, we estimate the explanatory power of several additional factors
urn:nbn:de:101:1-20080425295
Keywords: 330; Unternehmer; Selbstständige; Asiaten; Erfolgsfaktor; USA